Effects of teacher's personality traits on EFL learners' foreign language enjoyment. (December 2020) - Ahmadi-Azad, Shima; Asadollahfam, Hassan; Zoghi, Masoud
Abstract: Corresponding with the field of positive psychology and broaden-and-build theory, foreign language enjoyment (FLE) refers to the development of positive emotions in English as a foreign language (EFL) classrooms and encouraging EFL learners to utilize their potential to learn English. The present study investigated the role of Big Five personality traits of EFL teachers in developing learners' FLE. To this end, the NEO Five-Factor Inventory-3 and Foreign Language Enjoyment Scale were used to collect data from 107 Iranian EFL teachers and 1209 EFL learners, respectively. Results of the partial least squares structural equation modeling (PLS-SEM) revealed that the teachers' openness, extroversion, and agreeableness had a significant positive effect on the learners' FLE. However, their conscientiousness and neuroticism did not significantly predict the same. Therefore, it was concluded that the EFL teachers' personality traits could affect the learners' FLE. The results of this study could help expand the theories on positive psychology dealing with EFL learning. The findings of this study can benefit educational institutes, teacher-training centers, policymakers, and other stakeholders in the educational sector to consider EFL teachers' personality traits and their positive influence on language learning. Highlights: Effects of Big Five personality traits on EFL learners' FLE. partial least squares structural equation modeling (PLS-SEM) used for analysis. Openness, Extroversion, and Agreeableness positively influence EFL learners' FLE. Conscientiousness and Neuroticism did not positively and negatively influence EFL learners' FLE. FLE-private factor is more significant in the context of Iranian EFL classrooms than FLE-teacher and FLE-atmosphere factors.